Histomorphometrical analysis of bone formed after maxillary sinus floor augmentation by grafting with a combination of autogenous bone and demineralized freeze-dried bone allograft or hydroxyapatite - Boeck-Neto, R.; Gabrielli, MFR; Lia, Raphael Carlos Comelli [UNESP]; Marcantonio, E.; Shibli, J. A. (Amer Acad Periodontology, 2002)
Background: Maxillary sinus floor augmentation procedures are currently the treatment of choice when the alveolar crest of the posterior maxilla is insufficient for dental implant anchorage. This procedure aims to obtain enough bone with biomaterial association with the autogenous bone graft to create volume and allow osteo conduction. The objective of this study was to histologically and histometrically evaluate the bone formed after maxillary sinus floor augmentation by grafting with a combination of autogenous bone, from the symphyseal area mixed with DFDBA or hydroxyapatite.Methods: Ten biopsies were taken from 10 patients 10 months after sinus floor augmentation using a combination of 50% autogenous bone plus 50% dernineralized freeze-dried bone allograft (DFDBA group) or 50% autogenous bone plus 50% hydroxyapatite (HA group). Routine histological processing and staining with hernatoxylin and eosin and Masson's trichrome were performed.Results: the histomorphometrical analysis indicated good regenerative results in both groups for the bone tissue mean in the grafted area (50.46 +/- 16.29% for the DFDBA group and 46.79 +/- 8.56% for the HA group). Histological evaluation revealed the presence of mature bone with compact and cancellous areas in both groups. The inflammatory infiltrate was on average nonsignificant and of mononuclear prevalence. Some biopsies showed blocks of the biomaterial in the medullary spaces close to the bone wall, with absence of osteogenic activity.Conclusions: the results indicated that both DFDBA and HA associated with an autogenous bone graft were biocompatible and promoted osteoconduction, acting as a matrix for bone formation. However, both materials were still present after 10 months.
Keywords: Dental implants; Hydroxyapatite/therapeutic use; Regeneration grafts, bone; Maxillary sinus augmentation; Comparison studies